DIABETES: MODERN TREATMENTS AND LIFESTYLE (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This article provides a detailed review of the diagnosis, current treatment approaches, and lifestyle changes for diabetes. The focus is on therapies such as insulin and continuous glucose monitoring. Preventive measures such as healthy eating, physical activity, yoga, and stress management are also scientifically explained. The article discusses not only clinical approaches but also the effectiveness of lifestyle interventions in controlling diabetes.